2017
DOI: 10.7120/09627286.26.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Welfare assessment in traditional mountain dairy farms: above and beyond resource-based measures

Abstract: The Welfare Quality® project was one of the largest research undertakings into animal welfare. Despite animal-based measures (ABMs) being increasingly preferred over resource-based measures (non-ABMs), the Welfare Quality® protocol (WQ) for dairy cattle has a non-ABM, Ease of Movement that classifies housing systems using a threshold of 100 days of access to pasture or, inversely, of 265 days tethered. Since traditional transhumance to alpine pastures lasts for approximately 90 days most farms tend to be class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
4
10
1
Order By: Relevance
“…No cases of nasal discharge were observed and, in accordance with several studies carried out in indoor systems throughout Europe (e.g., Coignard et al, 2013;de Vries et al, 2013;Popescu et al, 2013;Zuliani et al, 2017), low prevalences for the other clinical measures (i.e., ocular discharge, vulvar discharge, hampered respiration, and diarrhea) were found throughout the assessments. Nevertheless, both ocular discharge and diarrhea were significantly more prevalent in DP than in BP and subsequently decreased again in AP.…”
Section: Animal-based Measuressupporting
confidence: 87%
“…No cases of nasal discharge were observed and, in accordance with several studies carried out in indoor systems throughout Europe (e.g., Coignard et al, 2013;de Vries et al, 2013;Popescu et al, 2013;Zuliani et al, 2017), low prevalences for the other clinical measures (i.e., ocular discharge, vulvar discharge, hampered respiration, and diarrhea) were found throughout the assessments. Nevertheless, both ocular discharge and diarrhea were significantly more prevalent in DP than in BP and subsequently decreased again in AP.…”
Section: Animal-based Measuressupporting
confidence: 87%
“…For example, Popescu et al (2014) observed on average 13.1% cows with a low BCS in loose houses and 10.2% in tiestalls. Zuliani et al (2017) observed 18.3% in Italian mountain farms. Heath et al (2014a) found on average 5.7% in a British study, whereas de Graaf et al (2017a) observed 5.5% in Belgium.…”
Section: Principle Of "Good Feeding"mentioning
confidence: 93%
“…The intensification of the dairy production over the past decades has left the Danish herds with an average herd size of 167 cows in 2015 compared to an average of 65.9 cows in 2000, rendering the larger herds with increased challenges regarding mortality [18] similar to their Nordic neighbors [19,20]. Additionally, herd size has also been associated with other management practices such as the choice of grazing or organic production status in smaller farms [21], an issue also evident in the Italian dairy production [22]. Larger production sites require a larger number of employees.…”
Section: Introductionmentioning
confidence: 99%